(One possible) future of multiphase flow modelling and simulation - Matar,OK (2018)
© 11th North American Conference on Multiphase Technology. All rights reserved. Understanding the dynamics of multiphase flows to enable their accurate and efficient prediction is of central importance in the oil-and-gas industry. Despite the significant advances that have been made in modelling these flows over a number of decades, however, numerous challenges, and open problems, remain. We present examples of progress made recently in the Multi-scale Examination of MultiPHase physIcs in flowS (MEMPHIS) programme aimed at providing reliable predictive tools. We also highlight the limitations of purely CFD-based approaches, and provide our perspective on potential predictive strategies based on a 'multi-fidelity' approach: a true fusion between modelbased and data-driven modelling. We are grateful for fruitful discussions with Prof. Panagiota Angeli (University College London), Dr Benoit Chachuat, Prof. Mark A. Girolami, Prof. Chris C. Pain (all from Imperial College London), and Prof. Mark J. Simmons (University of Birmingham, UK). The contribution and inspiration provided by Prof. Geoff F. Hewitt (Imperial College London), and the late Prof. Barry J. Azzopardi (University of Nottingham, UK) are also gratefully acknowledged; along with PA, CCP, MJS and OKM, GFH and BJA were the original co-investigators of the MEMPHIS programme. We also thank Drs Damir Juric and Jalel Chergui (both from LIMSI, CNRS, France), and Dr Seungwon Shin (Hongik University, South Korea) for their contribution to MEMPHIS. Finally, we would like to acknowledge financial support from the Engineering and Physical Sciences Research Council, UK, through the Multi-scale Examination of MultiPHase physIcs in flowS (MEMPHIS) Programme Grant (grant number EP/K003976/1), and from BP, and Procter & Gamble.